"Bacillus massilionigeriensis", a new bacterial species isolated from the human gut microbiota. (September 2016) - Tidjani Alou, Maryam; Brah, Souleymane; Delerce, Jeremy; Cadoret, Frédéric; Fournier, Pierre-Edouard; Lagier, Jean-Christophe
Abstract: We present a summary of the main characteristics of " Bacillus massilionigeriensis " strain Marseille-P2384 T (=CSUR P2384), isolated from the gut microbiota of a 44-month-old healthy girl from Niger.